2017
DOI: 10.1253/circj.cj-16-0756
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salt Loading on Plasma Osteoprotegerin Levels and Protective Role of Potassium Supplement in Normotensive Subjects

Abstract: Osteoprotegerin (OPG), a soluble member of the tumor necrosis factor (TNF) receptor superfamily, acts as a decoy receptor of the receptor activator of nuclear factor κ-B ligand (RANKL) and the TNF-related apoptosis-inducing ligand (TRAIL); RANKL and TRAIL are 2 cytokines of the TNF family mainly involved in bone metabolism; they are also found in other tissues, such as vascular smooth muscle cells. 13 OPG has been implicated in various inflammatory reactions and endothelial dysfunctions, which are also associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Osteoprotegerin is expressed in endothelial cells and play a pivotal role in vascular calcification and osteoporosis in different populations . In addition, osteoprotegerin may be associated with endothelial dysfunction by inducing the expression of ICAM‐1, VCAM‐1, and E‐selectin on endothelial cells and consequently promoting leukocyte adhesion to endothelial cells, which is considered to be an early step in endothelial dysfunction . This study is a cross‐sectional population‐based study needs to be further studied.…”
Section: Discussionmentioning
confidence: 97%
“…Osteoprotegerin is expressed in endothelial cells and play a pivotal role in vascular calcification and osteoporosis in different populations . In addition, osteoprotegerin may be associated with endothelial dysfunction by inducing the expression of ICAM‐1, VCAM‐1, and E‐selectin on endothelial cells and consequently promoting leukocyte adhesion to endothelial cells, which is considered to be an early step in endothelial dysfunction . This study is a cross‐sectional population‐based study needs to be further studied.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, previous studies have shown that ECM1 may interact with FBLN1 to participate in the composition of basement membrane proteins, and it may be critical for promoting angiogenesis [34]. Studies have indicated that RBP4 and DST may play a role in regulating endothelial barrier function and integrity in the body [35]. Therefore, changes in the expression levels of these proteins in patients with SAP may be closely related to the development of pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported potassium supplementation in normotensive individuals affects nitrogen oxide production by reducing asymmetric dimethylarginine levels during high salt loading 37 . Furthermore, potassium supplementation counteracts salt-associated osteoprotegerin elevation through oxidative stress reduction and endothelial function protection 38 . Overall, potassium supplementation might prevent salt-associated IR by inhibiting the expression of RBP4, which can stimulate the oxygen-reactive free radical generation and endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%